Effects of the chlorophyll leaf extract of Musa sapientum L. (Banana), Averrhoa bilimbi L. (Kamias) and Ixora coccinea L. (Santan) in the wound healing rate of Albino mice. - Kim, Eun Ji S. (2008)
ABSTRACT See Upload (BIO 987 2008)